Алгоритмическое и программное обеспечение для визуализации цветового представления видимого света заданного спектрального состава - Братчун, А. С. (ХНУРЕ, 2011)
This paper is devoted to the problem of adequate color representation of visible light with a given spectrum and quantitative comparison of different color representations. Software based on RGB, XYZ and Luv color space models was developed to solve the problem described.
Keywords: визуализация цветового представления; цвет